Identification of Giardia lamblia, Entamoeba histolytica and Cryptosporidium sp. in Feces of Diarrheal Patient at Puskesmas Jatinangor, SeptemberâNovember 2012 - Palani, Komathi; Faridah, Lia; Sumardi, H. Uun (Althea Medical Journal, 2015)
Background: Diarrhea is one of the main public health problems occurring in West Java. One of the affectedÂ areas is Subdistrict Jatinangor. Inappropriate management of sanitation facilities around Jatinangor areaÂ causes contamination of water. Cikeruh River is one of the water sources in Jatinangor Area, from whichÂ people obtain water for daily activities. Water borne illness due to poor sanitation condition can lead toÂ parasitic infection such as Giardia lamblia, Entamoeba histolytica and Cryptosporidium parvum whichcan cause a prolonged diarrhea. There has not been any study done regarding the presence of parasiticalÂ infection causing diarrhea around Jatinangor.Methods: In order to identify the parasitic infection, a descriptive study was carried out on 16 fecal samplesÂ collected from diarrheal patient who visited Puskesmas Jatinangor from SeptemberâNovember 2012. TheÂ parasites were checked by using wet mount methodResults: The parasites found were Entamoeba histolytica, Cryptosporidium parvum, but none of GiardiaÂ lamblia. There were also other findings such as Iodamoeba butschlii and Entamoeba coli.Conclusion: Positive findings of Entamoeba histolytica and Cryptosporidium parvum in diarrhea patients isÂ most probably due to contaminated water and food. Measures need to be done to improve sanitary conditionÂ in Cikeruh River to prevent diarrhea. [AMJ.2015;2(1):213â16]